Optical coherence tomography morphology and evolution in cblC disease‐related maculopathy in a case series of very young patients. Issue 8 (8th May 2017) - Bacci, Giacomo M.; Donati, Maria A.; Pasquini, Elisabetta; Munier, Francis; Cavicchi, Catia; Morrone, Amelia; Sodi, Andrea; Murro, Vittoria; Garcia Segarra, Nuria; Defilippi, Claudio; Bussolin, Leonardo; Caputo, Roberto
Abstract: Purpose: To describe the retinal structure of a group of patients affected by methylmalonic aciduria with homocystinuria cblC type, caused by mutations in the MMACHC gene, using spectral domain optical coherence tomography (SD‐OCT). Methods: Young patients ( n  =   11, age 0–74 months) with cblC disease, detected by newborn screening or clinically diagnosed within 40 days of life, underwent molecular analysis and complete ophthalmic examination, including fundus photography and SD‐OCT. In one case, we also performed fluorescein angiography (FA) and standard electroretinography (ERG). Results: Molecular analysis of the MMACHC gene fully confirmed cblC disease in nine of 11 patients. Two patients harboured only a single heterozygous pathogenic MMACHC mutation and large unbalanced rearrangements were excluded by array‐CGH analysis in both. All patients except two showed a bilateral maculopathy. In general, retinal changes were first observed before one year of age and progressed to a well‐established maculopathy. Measurable visual acuities ranged from normal vision, in keeping with age, to bilateral, severe impairment of central vision. Nystagmus was present in six patients. Spectral domain optical coherence tomography (SD‐OCT) showed macular thinning with severe alterations in outer, and partial sparing of inner, retinal layers. Conclusion: Patients affected by cblC disease may frequently show an early onset maculopathy with variable ophthalmoscopic appearance. Spectral domain optical coherence tomography (SD‐OCT) broadens the knowledge of subtle retinal alterations during the disease's progression and helps to shed light on the pathological mechanism of maculopathy development.